Direct Tax And Its Impact on the Gross Domestic Product (Gdp) of Nepal - Paudel, Udgar Kumar (Tribhuvan University Journal, 2025)
This article analyzes the relationship between direct tax and Nepal’s GDP. For the methodology, the Autoregressive Distributed Lag (ARDL) model is used for which the dependent variable is taken as GDP and the independent variables are taken as Corporate Income Tax (CIT) and Individual Income tax (IIT) respectively. The research uses time series data from 1990/91 AD to 2020//21 AD. This article found that a long-run relationship exists among the variables. There is a positive and significant relationship between IIT and GDP in the long run whereas there exists a positive but insignificant relationship between CIT and GDP in the long run. The model is free from heteroskedasticity and serial correlation, the functional form is correct and residuals are normally distributed. The CUSUM and CUSUMSQ test shows that the model is structurally stable. The article concludes that an increase in direct tax can contribute to an increase in GDP and it can be used as an option for Indirect tax which can hamper the poor.